Integument CYP genes of the largest genome-wide cytochrome P450 expansions in triatomines participate in detoxification in deltamethrin-resistant Triatoma infestans - Dulbecco, Andrea Belén (2018)
Insect resistance to chemical insecticides is attributed to a combination of different mechanisms, such as metabolic resistance, knockdown resistance, and the cuticular resistance or penetration factor. The insect integument offers an efficient barrier against contact insecticides and its role as penetration factor has been previously reported; however, there is no information about its potential function in the metabolic resistance. Cytochrome P450 genes (CYP) are highly expressed in the fat body of several insects and thus play a key role in their metabolic resistance. Here, we describe new members that belong to the highly genome-wide expanded CYP3093A and CYP4EM subfamilies in the Chagas disease vectors Rhodnius prolixus and Triatoma infestans. We modeled the docking of deltamethrin in their active site and detected differences in some amino acids between both species that are critical for a correct interaction with the substrate. We also knocked down the two constitutively most expressed genes in the integument of resistant T. infestans nymphs (CYP3093A11 and CYP4EM10) in order to find clues on their participation in deltamethrin resistance. This is the first report on the role of the insect integument in detoxification events; although these two CYP genes do not fully explain the resistance observed in T. infestans.